Hubungan Persepsi Hambatan dan Kemampuan Diri dengan Intensitas Konsumsi Tablet Fe pada Remaja Putri - Farichah Fa'ilal Chusna; Sulistiawati -; Irwanto - (AKADEMI KEBIDANAN DHARMA HUSADA KEDIRI, 2021)
The prevalence of anemia in adolescent girls aged 15-20 years in Indonesia attains 57.1%. The Ministry of Health targets the provision of Fe tablets to adolescent girls by 30% as an effort to prevent anemia in adolescent girls. However, proportion of consumption Fe tablets to adolescent girls in the working area of the Sidomulyo Health Center is still relatively low. This study aims to determine the relationship between perceived barriers and self-efficacy with the intensity of consumption of Fe tablets as an effort to prevent anemia. The method used in this research was cross sectional approach. The sample size is 155 respondents with the sampling technique used was random sampling. The results of this study indicate that there was a relationship between perceived barriers (p=0.003) and self-efficacy (p=0.000) with the intensity of consumption of Fe tablets.